IRREGULAR MARRIAGE AND COHABITATION IN SCOTLAND, 1855–1939: OFFICIAL POLICY AND POPULAR PRACTICE. (29th October 2015) - Unknown
Abstract: Scotland was unique in Western Europe in continuing to accord legal validity to irregular marriage until 1939 with one form of irregular marriage remaining legal until 2006. This article examines official attitudes to irregular marriage in Scotland in the period 1855–1939 as well as its incidence and popularity amongst the populace. The article argues that irregular marriage was narrowly defined by the authorities as meaning those irregular marriages that had been registered. Other forms of irregular marriage were often deemed to be cohabitation or concubinage which was regarded as morally reprehensible. However, authorities, including Poor Law officers, could also be flexible and sympathetic in their treatment of couples who lived together where the law was perceived to be rigid. Although it is impossible to quantify the numbers of couples who lived in non-registered informal unions, the evidence suggests that there were significant numbers but that in the majority of cases couples cohabited because they were unable to marry for legal, religious, or financial reasons.